2023
DOI: 10.3389/fpubh.2023.1092145
|View full text |Cite
|
Sign up to set email alerts
|

Early palliative care for solid and blood cancer patients and caregivers: Quantitative and qualitative results of a long-term experience as a case of value-based medicine

Abstract: IntroductionCancer patients and their caregivers have substantial unmet needs, that negatively impact the clinical outcome and quality of life. However, interventions aimed to address such needs are still suboptimal, failing to answer the recent healthcare call for the adoption of value-based models of care. In the case of incurable oncologic and hematologic cancers, a value-based model of care should plan advanced care on patients' needs and include the quality of death as an outcome. The integration of early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Previously published studies have highlighted the patient experience during NT for PDAC, as well as the caregiver experience in the setting of unresectable cancer, but little has been written about the caregiver experience during NT for PDAC. 8,23,24 In this cross-sectional mixed-methods analysis of caregivers' experiences and QOL during NT for PDAC, we found that caregivers' well-being is often characterized by emotional stress and anxiety, T A B L E 4 Representative quotes describing neoadjuvant therapy impact on different facets of the caregiver's daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies have highlighted the patient experience during NT for PDAC, as well as the caregiver experience in the setting of unresectable cancer, but little has been written about the caregiver experience during NT for PDAC. 8,23,24 In this cross-sectional mixed-methods analysis of caregivers' experiences and QOL during NT for PDAC, we found that caregivers' well-being is often characterized by emotional stress and anxiety, T A B L E 4 Representative quotes describing neoadjuvant therapy impact on different facets of the caregiver's daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Through the establishment of an honest and trusting relationship, the EPC team provides comprehensive symptom management; promotes illness understanding and prognostic awareness; supports patient and caregiver engagement in goals-of-care definition and treatment decisions making, including advanced care planning; facilitates coping; and monitors the family bereavement process through post-death family meetings. These interventions are provided through regular consultations with oncologists/hematologists and nurses ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Early palliative care (EPC) is a recent value-based model providing supportive care for patients who are facing a serious illness, to improve their quality of life (QoL) (1). In the oncohematology setting, EPC is defined as the early integration of palliative care (PC) into standard care, usually within 8 weeks from the diagnosis of incurable cancer (2)(3)(4)(5), in contrast with the model of the standard, late PC, which is usually delivered in the last days of life (6).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some versions of ePROMs have the feature of directly informing nursing staff about high symptom burden. As a result, nursing staff can take a direct response and initiate adequate symptom management immediately [9]. Since the use of PROMs facilitates the earlier detection of symptoms and needs, it may lead to the earlier integration of palliative care than before.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing ACPs receiving standard care with those who are receiving early palliative care, it becomes evident that they had less aggressive care at the end of life [10,11]. Moreover, the systematic use of PROMs leads to an improvement in communication between patients and healthcare providers [12,13], increased survival rates [14][15][16], and less visits to the emergency room [9].…”
Section: Introductionmentioning
confidence: 99%